The significance of multiple bacterial infections in lutjanus sp. in Malaysian marine cage culture system - Mansor, Nur Nazifah; Abdullah, Siti Zahrah; Nik Yusof, Nik Hiha; Ridzuan, Mohd Syafiq; Abdullah, Azila (2015)
The epizootiology of disease problems in Lutjanus erythropterus (Crimson snapper) was conducted in Pulau Langkawi Kedah, the northern state of Peninsular Malaysia, for a period of eight months until harvest due to reported continuous mortality of about 30% after two months introduction, incurring high economic loss. Infected fish was morbid, discoloured with haemorrhagic ulcers in dorsal areas and severe necrosis of caudal region. Monthly sampling revealed multiple Vibrio infections with variable prevalence rate during grow-out stage as shown in Fig.1.